EVALUATION OF THE FUNCTIONAL STATUS OF THE RUSSIAN POPULATION OF PATIENTSWITH RHEUMATOID ARTHRITIS ACCORDING THE DATA OF THE RAiSeR STUDY - O M Folomeyeva; E L Nasonov; I A Andrianova; E A Galushko; D V Goryachev; Tatiana Vasilyevna Dubinina; A P Zhornyak; O A Krichevskaya; Sh F Erdes (Научно-практическая ревматология)
Objective. To evaluate the functional status of patients with rheumatoid arthritis (RA) in Russia, to compare the distribution and associations between functional insufficiency (FI) and functional class (FC), as well as disability groups (DG), and to consider their impact of a number of the patients' demographic, social, and clinic characteristics. Methods. Rheumatologists from 27 cities and towns of Russia (a total of 30 centers) participated in the cross-sectional epidemiological study. The study included all patients with valid rheumatoid arthritis, who had consecutively turned to a polyclinic rheumatologist or who had been treated at hospital for 3 months. The demographic and social characteristics of a patient, his/her occupation, the onset and duration of RA, DG and a reason for its receiving, and the patient's clinicofunctional status at the study were recorded. Results. A total of 1504 patients, including 1271 women, were examined; their mean age was 53 years; the mean duration of the disease was 10.5 years; 80.4% were seropositive for rheumatoid factor; 94.3% patients had erosive arthritis (X-ray stages II-IV RA). High disease activity scores (DAS) were found; the mean DAS [Mean (SD)] was 5.44±1.18. Severe extraarticular manifestations were identified in 10% of cases. 63% of the RA patients were in FC III and IV; 67% had grades 2 and 3 FI, and 44.5% had DGs I and II. An association was found between FC and FI (r = 0.43; p < 0.0001), DG (r = -0.396; p